Strategi Guru Dalam Meningkatkan Motivasi BelajarSiswa Pada Mata Pelajaran Al-Quran Dan Hadis Di MtsNegeri Walen Simo Boyolali Tahun Pelajaran 2015 - 2016SKRIPSIDiajukan kepada - Hasan, Ismail (2016)
Teacher strategies are teaching a common approach that applies in many areas of materials and used to meet a variety of learning objectives. The learning activities are systematic activities and sequential. Therefore, learning activities should be planned well. Some competencies that should be controlled by teachers in particular are planned and designed of learning. A teachers need to have the competency to plan, implement, and evaluate learning of study result had a strategy of student's motivation giving to learn the spirit and improve students to achieve the expected goals, so that students would be more energetic, focused and serious in learning. Based on this background the writer can formulate the problem of how the strategy of teachers in improving student motivation on subjects Qur'an and Hadith at MTs Walen Simo Boyolali in the Academic Year 2015/2016. The purpose of this study was to describe strategies for teachers to improve students' motivation on the subjects of Koran Hadith at MTs Walen Simo Boyolali in the Academic Year 2015/2016. The benefits of this research are theoretically this study is to prove the existing theories in order to increase the vocabulary of science in education. While the practical benefits to add to the treasures of knowledge in the education field and as consideration for the next researchers to examine or discuss the other aspects. This study is qualitative field research. Based on research approach, this study included descriptive qualitative research. Data collection techniques used in this study, are observation, documentation, and interview methods. The data gained from the field, then be analyzed deductively. Based on the results of research and data analysis has been done, it can be concluded that In executing/implementing learning strategies on the subjects of the Qur'an and Hadith at MTs Walen Simo Boyolali, there are three stages: Firstly is pre instructional, that is before the lesson begins with open learning. Secondly, the instructional phase of the general activities undertaken at this stage is the delivery of content. Thirdly, the evaluation phase conducted to determine the level of instructional success. Keywords: Teacher's Strategy, Learning Motivation, Quran and Hadith Subjects.